2007
DOI: 10.1002/ppul.20579
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and exercise testing in adult survivors of congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is accompanied by pulmonary hypoplasia and structural abnormalities of the pulmonary vascular bed. It is unknown whether pulmonary function, exercise capacity, and gas exchange during exercise are impaired in adult CDH survivors. The objective of this study was to assess the long-term pulmonary function, exercise capacity, and gas exchange during exercise and relate these findings with quality of life. Of the 23 patients eligible for this study, 12 adult CDH survivors (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
1
25
1
Order By: Relevance
“…It is largely believed that alveolar function shows rapid improvement whereas vascular growth lags behind significantly [4,[7][8][9] . However, marked clinical improvement in respiratory symptoms, absence of significant ventilation-perfusion mismatch and its sequel in the form of pulmonary hypertension in the majority of survivors contradicts this finding [5,10,11] . Only a few studies have shown improved vascular remodeling parallel with the alveolar growth of hypoplastic lung in CDH survivors [12][13][14] .…”
Section: Introductionmentioning
confidence: 49%
“…It is largely believed that alveolar function shows rapid improvement whereas vascular growth lags behind significantly [4,[7][8][9] . However, marked clinical improvement in respiratory symptoms, absence of significant ventilation-perfusion mismatch and its sequel in the form of pulmonary hypertension in the majority of survivors contradicts this finding [5,10,11] . Only a few studies have shown improved vascular remodeling parallel with the alveolar growth of hypoplastic lung in CDH survivors [12][13][14] .…”
Section: Introductionmentioning
confidence: 49%
“…So far there is only one study describing potential consequences in adulthood. Exercise capacity and gas exchange parameters were normal in all 12 adult CDH survivors, indicating these patients have a normal pulmonary vascular bed [90].…”
Section: Pulmonary Hypertension and Follow-upmentioning
confidence: 90%
“…Similarly, fixed airway obstruction, such as subglottic stenosis, can produce a secondary pectus excavatum deformity, presumably as a result of long-term increased intrathoracic pressures during inspiration [47]. Up to 27% of children with congenital diaphragmatic hernia and unilateral lung hypoplasia develop scoliosis concave to the hypoplastic side by adulthood [42,48]. Whether this is related to the thoracotomy performed to correct the diaphragm defect early in life or the degree of unilateral lung hypoplasia or both is unclear.…”
Section: Does the Deformed Spine Grow Like The Normal One? Alain Dimementioning
confidence: 99%